Reduction of λ5‐Phosphinines. Issue 5 (13th October 2015) - Savateev, Aleksandr; Vlasenko, Yurii; Shtil, Nataliya; Kostyuk, Aleksandr
Abstract: A convenient method to easily prepare parent λ 3 ‐phosphinine from easily accessible λ 5 ‐precursors was developed. A series of λ 5 ‐phosphinines bearing heteroatom substituents OMe, SMe, and/or NMe2 at the phosphorus atom were prepared by electrocyclization of phosphahexatrienes generated in situ. Reaction conditions for the synthesis of λ 5 ‐phosphinines were optimized. The molecular structure of 1, 1‐dimethoxy‐λ 5 ‐phosphinine was determined by an X‐ray diffraction analysis. A series of reducing agents were tested in order to prepare λ 3 ‐phosphinine. 1, 1‐Dimethoxy‐λ 5 ‐phosphinine was reduced by LiAlH4 . The method of choice appeared to be the reduction of bis(dimethylamino)‐λ 5 ‐phosphinine with diisobutylaluminium hydride (DIBAL‐H) in 30 % overall yield starting from vinyl ethyl ether. Abstract : A set of parent λ 5 ‐phosphinines bearing OMe, SMe, and/or NMe2 substituents was synthesized. It was shown that they could be readily reduced to parent λ 3 ‐phosphinine. The most convenient method appeared to be reduction of readily available λ 5 ‐phosphinine featuring the dimethylamino groups. Its congener featuring the diethylamino group does not react under analogous conditions at all.